Life cycle assessment of sodium-ion batteries. Issue 5 (6th April 2016) - Peters, Jens; Buchholz, Daniel; Passerini, Stefano; Weil, Marcel
Abstract : Life cycle assessment for the production of a sodium-ion battery with a layered transition metal oxide and hard carbon. Abstract : Sodium-ion batteries are emerging as potential alternatives to lithium-ion batteries. This study presents a prospective life cycle assessment for the production of a sodium-ion battery with a layered transition metal oxide as a positive electrode material and hard carbon as a negative electrode material on the battery component level. The complete and transparent inventory data are disclosed, which can easily be used as a basis for future environmental assessments. Na-ion batteries are found to be promising under environmental aspects, showing, per kWh of storage capacity, environmental impacts at the lower end of the range published for current Li-ion batteries. Still significant improvement potential is given, especially by reducing the environmental impacts associated with the hard carbon production for the anode and by reducing the nickel content in the cathode active material. For the hard carbons, the use of organic waste can be considered to be promising in this regard. Nevertheless, when looking at the energy storage capacity over lifetime, achieving a high cycle life and good charge–discharge efficiency is fundamental. This represents the main challenge especially when competing with LFP–LTO type Li-Ion batteries, which already show extraordinarily long lifetimes.